Analisis Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Sepatu Converse - Within, Dorothea Helena; Langga, Lambertus; Dua Mea, Maria Helena Carolinda (SCIENTIFIC JOURNAL OF MANAGEMENT AND BUSINESS (SJMB), 2021)
This study aims to determine of dan brand image product quality against converse shoes purchase decisions (case study student/I at the Faculty of Economic. The type of research used is quantitative research. The data analysis technique used is is regression analysis multiple linear. Data collection was carried out by means ofinterviews and distributed questionnaires directly to 100 respondents.From the results of the development and testing of the instrument has been produced a goodquestionnaire tool (meets the requirements of validity, reliability). From the results t statistical test for the variable brand image and product quality has a value > and a significance value <0.05. This shows that the brand image and product quality affectspurchasing decisions. For the value of R square 0,290, this shows that the percentage analysis of the effect of brand image and product quality of 0.290%. Meanwhile, 0,710% is influenced by other factors which was not described in this study